Optimizing equine sperm quality: an alternative to single layer centrifugation for sperm isolation - Ashlee Jade Medica; Zamira Gibb; Robert John Aitken (Bioscientifica, 2024)
In vitro semen purification techniques have been developed that seek to mimic the in vivo selection process in order to generate the highest possible chance of oocyte fertilization following artificial insemination. Numerous methods have been developed to isolate functional spermatozoa for artificial insemination, yet only one method, single-layer centrifugation using commercial preparations like EquiPure, has been widely employed. In this study, we have introduced a novel approach for isolating spermatozoa and compared their quality to those isolated using EquiPure. The AI port system (Memphasys, Ltd. in Sydney, Australia) features a disposable cartridge with an inoculation chamber for depositing extended semen and a harvest chamber for extracting isolated spermatozoa. These chambers are separated by a 5 μm polyethylene terephthalate (PETE) membrane, allowing highly motile spermatozoa to migrate from the inoculation chamber to the harvest chamber over a 20-minute period. This migration effectively leaves behind seminal plasma and other cell types, such as leukocytes. Comparative analyses between spermatozoa isolated with the AI port and EquiPure demonstrated that, across all measured sperm parameters, including yield, vitality, motility, morphology, DNA fragmentation, and mitochondrial superoxide generation, the AI port-isolated cells exhibited comparable or superior performance, particularly in terms of DNA fragmentation. In summary, the AI port system demonstrates the potential to efficiently isolate high-quality spermatozoa, possibly offering a cost-effective and user-friendly alternative that may enhance the success rates of artificial insemination in breeding programs.